2009
DOI: 10.1103/physrevb.80.035330
|View full text |Cite
|
Sign up to set email alerts
|

Multiexponential photoluminescence decay of blinking nanocrystal ensembles

Abstract: We investigate the relationship between the multiexponential photoluminescence ͑PL͒ dynamics of large nanocrystal ͑NC͒ ensembles and the intensity intermittency ͑blinking͒ characteristic of single NCs. A general model is developed and a simple fitting form derived for the analysis of PL decay curves allowing the extraction of both the intrinsic radiative recombination rate and an intensity intermittence parameter. The analysis is applied to the PL of a series of Si-NCs embedded in silicon oxide matrices yieldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 77 publications
1
23
0
2
Order By: Relevance
“…Previous [2,12,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and our own [21] studies have shown that the integral PL time decay in Si-based nanostructures can be fitted by the well-known stretched exponential function…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Previous [2,12,36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and our own [21] studies have shown that the integral PL time decay in Si-based nanostructures can be fitted by the well-known stretched exponential function…”
Section: Optical Propertiesmentioning
confidence: 99%
“…21 Recently, the non-exponential PL dynamics of ensembles of localized centers have been linked to the PL intermittency, also called blinking, of individual centers whose emission is observed under continuous excitation conditions. 23,24 Blinking is observed in a variety of systems such as colloidal and self-assembled quantum dots (QDs) 23,[25][26][27] and Si nanocristals, 24 and is attributed to the formation of metastable, charge-separated (CS) dark states.…”
Section: Introductionmentioning
confidence: 99%
“…In some papers, β is shown being almost independent on emission energy in both PSi‐ and SiO 2 ‐embedded Si NCs . Other studies found β decreasing above and below 1.4 eV or above and below 1.7 eV in different forms of Si NCs. These observations suggest an optimum size of NCs emitting either near 1.4 or 1.7 eV with the narrowest distribution of decay constants (Section ).…”
Section: Resultsmentioning
confidence: 96%
“…Alternatively, single fluorophores of almost all light sources are well known for the phenomenon of intensity intermittence (“blinking”). Dunn et al suggested that PL relaxation is affected by blinking mechanism that produces sudden changes in PL intensity during continuous excitation which can lead to the SE shape of decay curve. 3) Direct consequence of indirect bandgap of Si is a broad homogeneous line at room temperature.…”
Section: Resultsmentioning
confidence: 99%